Regulations, Policies and Conflicts Due to Agrochemicals in Salta, Argentina - Schmidt, Mariana Andrea (2021)
The consolidation of agribusiness in Argentina since the end of the 20th century can be analyzed in its multiple and diverse consequences: environmental impacts due to the deforestation of native forests; social conflict over the forcing out and destruction of rural and indigenous production and reproduction methods; health effects since exposure to pesticides, among the main ones. Based on secondary information sources and in-depth interviews, the article aims to contribute to the understanding of the environmental and sanitary impacts linked to fumigation with agrochemicals in Salta, a province of northern Argentina which in recent years has incorporated large areas into agricultural production and presents ecological and social characteristics that differ from the Pampas region. This research focuses on a critical characterization and analysis of the regulatory frameworks and public policies on that matter, as well as in a survey related to conflicts. The main findings show that in Salta different legal frameworks regulate the use of agrochemicals, while state agencies are meant to implement and monitor such regulations. However, the study compiles numerous situations that illustrate the emergence and path of certain conflicts that, with varying levels of visibility and intensity, problematize the effects on human health and ecosystems at the local levels.